A functional variant on 20q13.33 related to glioma risk alters enhancer activity and modulates expression of multiple genes. Issue 1 (22nd November 2020) - Ali, Mourad Wagdy; Patro, C. Pawan K.; Zhu, Jacqueline Jufen; Dampier, Christopher H.; Plummer, Sarah J.; Kuscu, Cem; Adli, Mazhar; Lau, Ching; Lai, Rose K.; Casey, Graham
Abstract: Genome‐wide association studies (GWAS) have identified single‐nucleotide polymorphisms (SNPs) associated with glioma risk on 20q13.33, but the biological mechanisms underlying this association are unknown. We tested the hypothesis that a functional SNP on 20q13.33 impacted the activity of an enhancer, leading to an altered expression of nearby genes. To identify candidate functional SNPs, we identified all SNPs in linkage disequilibrium with the risk‐associated SNP rs2297440 that mapped to putative enhancers. Putative enhancers containing candidate functional SNPs were tested for allele‐specific effects in luciferase enhancer activity assays against glioblastoma multiforme (GBM) cell lines. An enhancer containing SNP rs3761124 exhibited allele‐specific effects on activity. Deletion of this enhancer by CRISPR‐Cas9 editing in GBM cell lines correlated with an altered expression of multiple genes, including STMN3, RTEL1, RTEL1‐TNFRSF6B, GMEB2, and SRMS . Expression quantitative trait loci (eQTL) analyses using nondiseased brain samples, isocitrate dehydrogenase 1 ( IDH1 ) wild‐type glioma, and neurodevelopmental tissues showed STMN3 to be a consistent significant eQTL with rs3761124. RTEL1 and GMEB2 were also significant eQTLs in the context of early CNS development and/or in IDH1 wild‐type glioma. We provide evidence that rs3761124 is a functional variant on 20q13.33 related to glioma/GBM risk that modulates the expression of STMN3 and potentially other genes across diverse cellular contexts.